Generalized integral theorems for quaternionic G-monogenic mappings - Kuzmenko, Tetyana S.; Shpakivskyi, Vitalii S. (Journal of mathematical sciences (New York, N.Y.), 2017)
For G -monogenic mappings taking values in the algebra of complex quaternions, we generalize some analogues of classical integral theorems of the holomorphic function theory of complex variable (the surface and curvilinear Cauchy integral theorems).